The Effect Of Working Capital Management, Leverage, And Institutional Ownership On Profitability With Company Size As A Moderation Of Consumer Goods Companies Listed On The Indonesia Stock Exchange In The Period 2019-2023 - Ihsan Trianto (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Economic progress in Indonesia cannot be separated from the contribution of various industries operating domestically. One sector that plays an important role in Indonesia’s economic development is the consumer goods sector. This study uses a quantitative approach. The data used in this study are secondary data obtained from the annual financial reports of consumer goods companies that have gone public from 2019-2023. The population in this study were all consumer goods companies listed on the IDX in 2019 - 2023, namely 94 companies. This study uses a non-probability sampling method with a purposive sampling technique. The data analysis method used in this study is Moderated Regression Analysis (MRA). The results of the study show that working capital management has an effect on profitability, leverage has an effect on profitability, institutional ownership has an effect on profitability, company size cannot moderate the effect of working capital management on profitability, company size can moderate the effect of leverage on profitability, company size cannot moderate the effect of institutional ownership on profitability